Assessing the Impacts of land Use Change on Carbon Sequestration: A Comprehensive Analysis for Kochi City, India - Thomas Mathew; Shanmuga Priya Gnanasekaran (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Land use typologies play a pivotal role in determining the carbon sequestration capacity of urban ecosystems. As human activities continue to reshape landscapes, understanding the impact of different land uses on carbon storage is crucial for developing effective climate change mitigation strategies for cities. This paper aims to analyse the relationship between land use typologies and carbon sequestration. Carbon sequestered in the selected city i.e., Kochi is quantified using the InVEST Carbon Storage and Sequestration model (Integrated Valuation of Ecosystem Services and Tradeoffs), coupled with remote sensing. The model uses input data on carbon pools including above-ground, below-ground, soil biomass, and dead carbon matter. The change in carbon sequestration with change in land use between 2003 and 2023 is calculated. The study reveals that there has been a reduction in wetland areas by 59 % which leads to 63% less sequestration of carbon highlighting the implication of land use on carbon sequestration.